Seismic Assessment of the Historical Sutlu Minaret Mosque - Maras, Muslum Murat; Ozmen, Alper; Sayin, Erkut; Ayaz, Yasar (Budapest Univ Technology Economics, 2022)
Historical masonry structures that connecting the past to the present have great importance because they represent the experiences and characteristics of various cultures. Therefore, the protection of historical structures is important. In this study, the structural response of the historical masonry Mosque was evaluated through dynamic analyses. For this purpose, the Sutlu Minaret Mosque which is located in Malatya, Turkey, was investigated. The three-dimensional model of the historical mosque was generated with ANSYS software. The material properties of the mosque were obtained with experimental tests. The time history analyses were used to obtain the seismic behavior of masonry mosque. In the time history analyses, six different strong ground motion records, including the 2020 Elazig earthquake, were used. After the analysis, displacement and stress values in the mosque were given. The absolute peak displacement value among these earthquake records was obtained from the 1999 Duzce earthquake and the highest principal compressive and tensile stress values were determined for the 2010 Darfield earthquake. Also, the crack regions which occurred in the mosque after the 2020 Elazig earthquake were compared with the dynamic analysis result of the 2020 Elazig earthquake. The crack regions formed after the Elazig earthquake are similar to the possible crack regions formed after the dynamic analysis.
Keywords: historical masonry mosque; time history analysis; finite element analyses; structural assessment